A double-blind, placebo controlled study to assess the clinical and microbiological effects of a probiotic lozenge as an adjunctive therapy in the management of chronic periodontitis - Grace Tara Paul; D Gandhimadhi; S P. K Kennedy Babu (Wolters Kluwer Medknow Publications, 2019)
Background: The study was conducted to determine the effect of a probiotic lozenge as an adjunct to scaling and root planing in patients having chronic generalized periodontitis in a double blinded, placebo-controlled design. Materials and Methods: A total of 30 chronic generalized periodontitis patients, in the age group of 25-60 years were recruited for the study. Clinical parameters of plaque index (PI), bleeding index (BI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL) and microbiological levels of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis and Prevotella intermedia were assessed at baseline, 3, 6, and 12 weeks. All patients underwent scaling and root planing (SRP) at baseline and were recalled after 3 weeks. At 3 weeks, the patients were prescribed either probiotic or placebo lozenges for a 3-week period. Statistical analysis was conducted for clinical and microbiological parameters. Results: The PI, PPD, and CAL significantly reduced in both the groups from baseline to 12 weeks. GI and BI reduced significantly at 3 and 6 weeks in the probiotic group and at 3, 6, and 12 weeks in the placebo group. There was a significant decrease in the assayed periopathogens in both the probiotic and placebo groups at all-time intervals. Conclusions: The present study did not show a significant difference of using probiotic over SRP. As the duration of the study was limited to a period of 3 months, the need to conduct large multicenter studies is warranted to substantially validate the use of probiotics in the management of chronic periodontitis.